Factors affecting uptake of postmortem examination in the prenatal, perinatal and paediatric setting. (21st March 2017) - Lewis, C; Hill, M; Arthurs, OJ; Hutchinson, C; Chitty, LS; Sebire, NJ
Abstract : Background: Postmortem examination is the single most useful investigation in providing information to parents about why their baby or child died. Despite this, uptake remains well below the recommended 75%. Objective: To address the question 'what are the barriers and motivators to perinatal, prenatal and paediatric PM examination?' Search strategy: Key databases including Pubmed and CINAHL; Cochrane library, websites of relevant patient organisations, hand search of key journals, first and last authors and references. Selection criteria: Peer‐reviewed qualitative, quantitative or mixed methods research examining factors affecting uptake or decline of perinatal or paediatric postmortem examination. Data collection and analysis: Narrative synthesis; findings were compared across studies to examine interrelations. Main results: Seven major themes describing barriers to postmortem uptake were identified: dislike of invasiveness, practicalities of the procedure, organ retention issues, protective parenting, communication and understanding, religion and culture and professional or organisational barriers. Six major themes related to factors which facilitated parental consent were identified: desire for information, contributing to research, coping and well‐being, respectful care, minimally invasive options, and policy and practice. There were a number of themes in the literature that reflected best practice. Conclusion: Findings highlight the need for better health professional education and the fact some concerns may be mitigated if less invasive methods of postmortem were routinely available. New consent packages and codes of practice may have a positive impact on perception of examination after death. The landscape is changing; further research is necessary to assess the impact on postmortem uptake rates. Tweetable abstract: Systematic review to explore the barriers and motivators to perinatal, prenatal and paediatric postmortem examination. Tweetable abstract: Systematic review to explore the barriers and motivators to perinatal, prenatal and paediatric postmortem examination.